English Communication Skills Training for Students through the Communicative Language Teaching Method - Soni, Muhammad; Fajriah, Yustika Nur; Nugraha, Irsyad; Nurjamin, Lucky Rahayu (Fakultas Kewirausahaan Universitas Garut, 2025)
Given the challenges and needs mentioned above, English language skills training through speaking is a strategic and crucial step for students. This community service activity aims not only to improve their English skills but also to prepare them to face the challenges of an increasingly connected global world. The methods employed include role-playing and group-based projects. The results of this community service activity identified students as possessing English language skills through the CLT method, which plays a role in shifting their learning paradigm from passive and focused on mastering grammatical structures to active, communicative, and meaning-oriented. This training opens new insights into how to learn and use English. English communication skills training through the CLT method successfully equips students with language competencies that are not only theoretical but also practical and contextual. Thus, through this method, students learn to use English as a real-life communication tool that can support academic activities, social life, and prepare them for entering the global workforce.